Role of outer membrane histopathology and comparison of clinico-radiological aspects of chronic subdural hematoma in different age groups: a retrospective study - Potdar, Nilesh Vishnu; S., Suresh Kumar; Kaplinghat, Bhavadasan (International Surgery Journal, 2017)
Background: The incidence of chronic subdural hematoma (CSDH) has been found to increasing in younger patients. This study was aimed to evaluate the role of outer membrane histopathology and comparison with the clinic-radiological aspects of chronic subdural hematoma in different age groups. Methods: Cases of CSDH admitted to the Neurosurgery department during January 2014 and December 2016 were included in the study. They were analyzed clinically, radiologically like site, size, thickness in computed tomography, the attenuation value and midline shift. Histopathological features were also recorded. Cases of acute and chronic sub dural hematoma which were managed conservatively irrespective of age and sex were excluded from the study. Results: Total 196 patients were included with median age of 66 yrs. The most common histopathological type of membrane was the scar inflammatory membrane (Type IV) in 43% of cases followed by hemorrhagic inflammatory membrane (Type III) in 31% of cases while the scar inflammatory type of membrane (Type II) was in 26% of cases. Young age group patient having less thickness of hematoma (<2cm) and having hyper density on CT scan. Old age group had more thickness(3.2cm) and mixed density with multiple layering. Conclusions: Young age group patient having less thickness of hematoma and hyper density compared to old age group. Recurrence and bilateral disease were more common in old age group associated with brain atrophy. Histopathological study completes the spectrum of CSDH in terms of severity of disease and overall prognosis of patient.